Βουλγαριας - σερβιας πολέμου: військова експансія дунайських болгар на терени Західних Балкан у 836-889 рр. - Калініченко, Віталій (Чернівці, Видавництво "Прут", 2015)
Стаття присвячена аналізу військових походів дунайських болгар на Західні Балкани у 836-889 рр. На основі писемних та археологічних джерел встановлюється, що основними напрямками військової експансії болгарських військ були території середньовічної Сербської держави, яка включала в себе області Рашка, Дукля, Травунія, Паганія, Захумле, Боснія, а також частину Хорватії. Крім того, автором висвітлюються військові дії болгарських військ у Македонії та Кутмічевіці. Окрема увага приділена аналізу воєнної експансії болгар на територію сербського Поморав’я, Подунав’я та Помор’я. Окрім того, автором розглядається болгарсько-хорватський військовий конфлікт 50-х рр. ІХ ст. В цьому аспекті важливими є знахідки предметів озброєння епохи середньовіччя (ІХ-Х ст.) з міст Джердап, Бєлград, Ніш, Раc, Малі Зворнік, областей Срем, Бранічево, середньовічних могильників та укріплень у сербському Помор’ї, середньовічних фортець та хорватських могильників у Далмації та Лібурнії. The article analyzes the military campaigns Danube Bulgarians in the Western Balkans in 836-889 years. Based on written and archaeological sources states that the main directions of the military expansion of the territory of the Bulgarian troops were medieval Serbian state, which included the Raska region, Duklja, Travunija, Paganija, Zachlumia, Bosnia, and a part of Croatia. Furthermore the author highlights the fighting Bulgarian troops in Macedonia and Kutmichevitsa. Special attention is paid to the analysis of military expansion on the Bulgarian territory Serbian Pomorav’ya, Danube and Pomorje. Furthermore the author is considered a Croatian-Bulgarian military conflict of the 50’s IX century. In this respect, are important finds of armaments of the Middle Ages (IX-X century) in Dzherdap, Belgrade, Nis, Ras, Mali Zvornik, areas of Srem, Branichevo, medieval fortifications and cemeteries in the Pomorje, medieval fortresses and cemeteries Croatian in Dalmatia and Liburnia. At the beginning of the IX-th century Khan Krum conquered the territory of central and eastern Avar Khanate by connecting them to Khanate. As a result of this war was the neighbor state of Bulgarians Frankish Empire, which, in turn, defeated Northwest territories Avar Khanate. The border between the states placed on the middle reaches of the river Danube. In addition, Khan Krum successfully fought with Byzantium. It was under his reign the first Bulgarian state strengthened its border with the medieval Serbian state, which was the springboard Pomorav’ya. War Krum in the valley Struma river gave impetus to the military expansion in the Adriatic state. For Krum successor, Khan Omurtag important and key military actions carried out in the north-west. It is in this context it is necessary to recall the first time in South Pannonia which became a springboard for military expansion in medieval Serbia from the north. By the mid 30’s IX century was created a successful springboard for expansion of Bulgarian military forces in the Western Balkans, where the Serbian state. The latest in the IX-X centuries covered vast areas and had a fairly good geographical location. Getting Bulgarian military campaign against the Serbs came in the reign of prince (archont) Vlastimir (830-851), who relied mainly on domestic army, as the war with the Bulgarians from anyone independent. In the middle of the IX-th century except Serbian, powerful enough army were Croats who were strongly influenced by the East Frankish kingdom. In addition, the Croatian prince Trpimir was dissatisfied successful wars Bulgarians in Serbia and feared an attack on their land. Thus, in the middle of the ninth century. in the Western Balkans has developed quite difficult foreign policy situation. The medieval Serbian state was squeezed from all sides, and was forced to fight wars of the first Bulgarian state in the east, southeast, north and Croats, advancing from the west and northwest. Overall, we note that the Bulgarian-Serbian war IX-th century, despite the wide base, still insufficiently studied. Yes, raw, unstructured materials from archaeological remains of medieval castles located in the Western Balkans. Latest items are weapons, ornaments, parts lap headsets, the rider and the horse equipment and so on. Thus, the most important medieval fortifications where weapons found IX-X centuries are Belgrade, Nis, Ras, Mali Zvornik, regions Srem, Branichevo, castles in Pomorje etc. Written ьsources are reportedly Simeon Logofet and Constantine Porphyrogenitus («De administrando Imperio»). Thus, in the IX-th century there is a massive military expansion of the First Bulgarian state in the Western Balkans. The most important ranked Serb campaign of Bulgarian rulers. The material proof of the military campaigns Danube Bulgarians and Serbs in the land development Serb areas they are finding artifacts Bulgarians. Important among them are armaments that indicate a strong enough military organization of the First Bulgarian state in the IX-th century. But despite the fact that during the campaign’s 836-889. Bulgarian troops suffered defeat, one can assume that the Serbian army in the IX-th century in no way inferior to the Bulgarian and may be more advanced and modernized at that time. Constant contacts with Byzantium, Franks, Croats, Arabs had an impact on the formation of the Serbian military culture. Bulgarian played an important role Croat military conflict. Most likely, because of Serb and Croat campaigns Bulgarians became acquainted with several new types of weapons, which are primarily ranged weapons and Pole weapon. As a result of military campaigns 836-889 years the First Bulgarian state has significantly expanded its borders to the west and, most importantly, met with the military culture of the Serbs, Croats and francs, reflected in the subsequent military campaigns Bulgarian troops in Central and Eastern Europe in the late IX-X-th century.
Βουλγαρίασ – σερβίασ πολέμου: военная экспансия дунайских болгар на территорию Западных Балкан в 836-889 рр.
Βουλγαρίασ – σερβίασ πολέμου: military expansion of the Danube Bulgaria to the Western Balkans in 836-889
Keywords: Перша Болгарська держава; середньовічна Сербська держава; Західні Балкани; воєнна експансія; предмети озброєння